THE PROMOTION OF POPULAR AND TRADITIONAL GAMES IN ELEMENTARY EDUCATION OF BOIRO´S MUNICIPALITY (A CORUÑA) - José Eugenio Rodríguez Fernández; José María Pazos Couto; José Palacios Aguilar (Sportis, 2015)
The current curriculum for elementary education in the autonomous community of Galicia includes the importance of Galician traditional and popular games and sets the content to work on all this educational stage, mainly based on recognition, practice, research, history and cultural value that this type of practice has for the students of this community. The skittles´s game in Boiro in the past had a great repercussion among the people, being probably the principal entertainment of the Boiro´s people in the first third of the 20th century. The objective of this study is to analyze the promotion, dissemination and practice of popular and traditional games in general and the skittles´s game in particular into the elementary schools of the municipality of Boiro, using qualitative techniques for data collection, the personal interview to be the main tool used for this purpose. The results of the study show the need to deepen the work of these recreational practices in education centers, nowadays more oriented to comply with the minimum laid down in the official curriculum that give true meaning to games that are part of the history and culture of the village of Boiro, still skittles´s game clearer reference in this regard. Public administrations must be coordinated to implement a much more ambitious project of recovery of this kind of practice, in which the school should be considered as the starting point.